Urenhedsforestillinger i den monastiske kultur - Schönbeck, Oluf (Religionsvidenskabeligt Tidsskrift, 1997)
A number of statements by the eleventh centurt ascetic Peter Damian concerning purity, impurity and purification are interpreted by means of the so-called Container Schema formulated by George Lakoff and Mark Johnson. According to Lakoff and Johnson humans experience teir bodies as containers and as things in containers. Containers are characterized by the following structural elements: interior, boundary, exterior. Peter Damian is shown to describe impurity as a state of defilement, disease of bodily injury - all phenomena that are caused by a threatened or an actual breakdown of the boundary of the container, i.e. the human skin, the main purpose of which is to separate the interior from the m enacing exterior. Basically then, impurity is seen as a result of an invasion of the body by foreign substances through the natural orifices, e.g. the senses, or through lesions - substances that may in their turn bring about unwanted discharges in the shape of e.g. semen or - in a metaphorical sense - sinful behaviour. Acts of purification are described by Damian in terms of the same container metaphor. Finally, it is suggested that the container metaphor may serve as a tool in analysing ideas of impurity outside a Christian, monastic context.